(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The evaluation process in the sports field receives a lot of attention from researchers and specialists in the field of measurement and evaluation in physical education and sports sciences, as it is one of the basic components of the learning and training process and an integral part of it. Evaluation gains this importance by providing continuous nutrition and monitoring negatives in order to avoid them, correct weakness, treat it, and enhance Aspects of strength and benefiting from them, it includes an estimate of performance and the amount of outcome that expresses the changes achieved through the practice of education and training programmes, and then issuing judgments in light of specific considerations of the specifications of that performance. The current research aims to evaluate the combinatorial abilities and offensive skills of handball players, which number (25) players. To achieve this goal, the researcher used the descriptive approach in the style of (survey, correlations) because it is one of the most appropriate approaches to the nature of the research problem. The research population was identified as 25 players from the Al-Daghara Handball Club. The researcher also used tests that measure combinatorial abilities and offensive skills as main tools for collecting data. After a series of field procedures represented in ensuring the validity of the tests, by verifying the conditions for their scientific characteristics (honesty, reliability, objectivity), the researcher began applying the tests for combinatorial abilities and offensive skills and obtaining their results, extracting their standard scores, setting standard levels, and then building The evaluative model (the evaluative model) and in light of the research results, the researcher reached some conclusions, the most important of which are: It is possible to rely on the lateral map (the evaluative model) as an objective scientific method in evaluating combinatorial capabilities and offensive skills.